One-step fabrication of robust and anti-oil-fouling aliphatic polyketone composite membranes for sustainable and efficient filtration of oil-in-water emulsions. Issue 47 (26th November 2018) - Zhang, Lei; Cheng, Liang; Wu, Haochen; Yoshioka, Tomohisa; Matsuyama, Hideto
Abstract : A robust and anti-oil-fouling aliphatic polyketone composite membrane for sustainable and efficient filtration of oil-in-water emulsions. Abstract : Oil-fouling resistance of membranes is crucial for enabling efficient oil/water separation. Starting with an aliphatic polyketone (PK) polymer with intrinsic intermediate hydrophilicity and good membrane formation ability, a robust PK composite membrane with the ideal abrasion-resistant and chemical-resistant super-anti-oil-fouling property was effortlessly prepared by a simple one-step non-solvent induced phase separation (NIPS) process, with the polyvinyl alcohol (PVA) additive introduced as a pore-former and more importantly a hydrophilicity enhancer to perfect the underwater oil-repellency and a nylon mesh as a reinforcing support. Molecular dynamics (MD) simulations revealed that the intermolecular and intramolecular hydrogen bonds are responsible for the stable confinement of PVA within the PK matrix, leading to the all hydrophilic PK–PVA mixed surface chemistry. Fouling-resistant membrane filtration of oil-in-water emulsions was readily achieved in the cross-flow mode with a high flux up to 420 L m −2 h −1 at 0.1 bar and a high flux recovery of 93–96% being maintained, even for the highly adhesive and highly fouling soybean oil emulsions (up to 100 000 ppm). The prepared membrane with excellent comprehensive performance and high cost-effectiveness is very promising in sustainable treatment of difficult oil-in-water emulsions.